(untitled) (Bangladesh Journal of Endosurgery, 2014)
Bilateral ureteral triplication is a very rare form of congenital urinary tract anomaly; so far, less than 10 cases have been reported worldwide. We report an infant with bilateral complete duplex kidneys and a rare variant of Type II bilateral ureteral triplication. The diagnostic challenges and successful laparoscopic management are discussed. DOI: http://dx.doi.org/10.11593/bje.2013.0103.0021 Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 16-19